Prevalence and causes of vision loss in Latin America and the Caribbean in 2015: magnitude, temporal trends and projections - Leasher, Janet L.; Jonas, Jost B. (British journal of ophthalmology, 2019)
OBJECTIVE: To estimate the prevalence and causes of blindness and vision impairment for distance and near in Latin America and the Caribbean (LAC) in 2015 and to forecast trends to 2020. - METHODS: A meta-analysis from a global systematic review of 283 cross-sectional, population-representative studies from published and unpublished sources from 1980 to 2014 in the Global Vision Database included 17 published and 6 unpublished studies from LAC. - RESULTS: In 2015, across LAC, age-standardised prevalence was 0.38% in all ages and 1.56% in those over age 50 for blindness; 2.06% in all ages and 7.86% in those over age 50 for moderate and severe vision impairment (MSVI); 1.89% in all ages and 6.93% in those over age 50 for mild vision impairment and 39.59% in all ages and 45.27% in those over 50 for near vision impairment (NVI). In 2015, 117.86 million persons were vision impaired; of those 2.34 million blind, 12.46 million with MSVI, 11.34 million mildly impaired and 91.72 million had NVI. Cataract is the most common cause of blindness. Undercorrected refractive-error is the most common cause of vision impairment. - CONCLUSIONS: These prevalence estimates indicate that one in five persons across LAC had some degree of vision loss in 2015. We predict that from 2015 to 2020, the absolute numbers of persons with vision loss will increase by 12% to 132.33 million, while the all-age age-standardised prevalence will decrease for blindness by 15% and for other distance vision impairment by 8%. All countries need epidemiologic research to establish accurate national estimates and trends. Universal eye health services must be included in universal health coverage reforms to address disparities, fragmentation and segmentation of healthcare.
Published Online First: 12 September 2018
Collaborators GBD Vision Loss Expert Group Members: Jost Jonas [und 99 weitere]
Gesehen am 01.08.2019